Penerapan Model Based Learning (PBL) dalam Pembelajaran Tematik Terpadu di Kelas 5 Sekolah Dasar - Lolita Anna Risandy; Septiana Sholikhah; Putri Zudhah Ferryka; Anggi Firnanda Putri (Institut Nalanda, 2023)
This study aims to explore the application of Model Based Learning (PBL) in Integrated Thematic Learning in Grade 5 Elementary Schools. The research method used was a literature study, by conducting a search for relevant literature on the application of PBL in the context of integrated thematic learning in grade 5 of elementary school. Literature analysis was conducted to identify the benefits, challenges, and recommendations that emerged from previous research. The results of the study show that the application of PBL in integrated thematic learning in grade 5 elementary schools provides significant benefits, such as subject integration, contextual learning, development of critical thinking skills, higher student engagement, collaboration and communication, and development of student creativity. However, Therefore, a differentiation approach, involving parents, collaboration between teachers, as well as a well-planned approach and good support are needed to carry out PBL effectively in grade 5 of elementary school. This research provides useful insights for educators and practitioners in implementing PBL in Integrated Thematic Learning in Grade 5 Elementary Schools.